The Tatar Epic “Edigü”: An Echo through the centuries - L.Kh. Mukhametzianova (Золотоордынское обозрение)
Objective: To study the origin and further development of the Tatar dastan, “Edigü”; to reveal the connections between the historical epic and the history of the Tatars from the fifteenth to the twenty-first century. Research materials: This study is based on a wide range of primary written sources, stored in the funds of the Center for Written and Musical Heritage of the G. Ibragimov Institute of Language, Literature and Art of the Tatarstan Academy of Sciences. The author focuses on the history of recording and the further and final formation of the “Edigü” epic; she analyzes the processes of genre inertia and transformation based on the material of the dastan’s texts. She also raises the question of the spread over time and territory of “Edigü” among the Tatars, along with the continuity of the main idea in this dastan from oral tales to its later versions. The objects for this research are the archival as well as published Tatar-language texts of the epic “Edigü” in various versions, directly related to the Volga region and other regions inhabited by the Tatars. Results and novelty of the research: The author refers to the problems of the genesis of the national epic “Edigü”, revealing the commonalities between various Tatar variants of the famous dastan successively passing through the centuries. The epic’s plot is found both in the Volga region and in Siberia, as evidenced by written sources that have survived to our time in which the dastan’s variants are recorded. Once orally performed among the Tatars, the historical and heroic epic found its written form in the twentieth century. The study systematically proved that epics based on ethnic traditions, subordinated to epic patterns and in the form of oral epic tales and songs, including in the famous epic “Edigü”, were widespread among Tatars since the fifteenth century. For the argumentation of her position, the author refers to recorded archival documents. The study of the Tatar epic “Edigü” in comparison with all possible variants suggests that it not only remains relevant to the present day in Tatar folk art, but also contributes to a more detailed study of the history of the Golden Horde.